Pengaruh Tingkat Kualitas Layanan, Faktor Kepuasan, dan Motivasi Belajar terhadap Prestasi Mahasiswa - Raden Bambang Sumarsono; Maisyaroh Maisyaroh; Desi Eri Kusumaningrum (Faculty of Education Universitas Negeri Malang, 2021)
Abstract: This study aims: (1) to describe the level of service quality, the level of student satisfaction, learning motivation, and the level of academic and non-academic achievement of students, and (2) to determine the model of the structural relationship between variables. This research design uses quantitative research. The research population consisted of all students, which was 3,702. Sampling using a simple proportional random technique, through this technique obtained a research sample of 361. Meanwhile, for data collection using a questionnaire technique. As for data analysis using descriptive and correlational analysis techniques with Structural Equation Model (SEM). The results of the analysis show that: 1) the level of service quality is in the sufficient category; 2) student satisfaction with services in the sufficient category; 3) students’ learning motivation is in the low category; 4) the level of student achievement in the low category; 5) there is an effect of service quality on student satisfaction; 6) there is an effect of service quality on student learning motivation; 7) there is an effect of the level of satisfaction on student learning motivation; 8) learning motivation has no effect on student achievement; 9) there is a direct or indirect influence between the level of service quality on achievement through student learning motivation; and 9) there is a direct or indirect influence between satisfaction and achievement through student learning motivation. Abstrak: Penelitian ini bertujuan: (1) mendeskripsikan tentang tingkat kualitas layanan, tingkat kepuasan mahasiswa, motivasi belajar, dan tingkat prestasi akademik dan non-akademik mahasiswa, dan (2) mengetahui model hubungan struktural antar variabel. Rancangan penelitian ini menggunakan penelitian kuantitatif. Populasi penelitian terdiri atas seluruh mahasiswa yaitu sebesar 3.702. Pengambilan sampel dengan menggunakan teknik proposional acak sederhana, melalui teknik tersebut diperoleh sampel penelitian sebesar 361. Sementara itu, untuk pengambilan data dengan menggunakan teknik angket. Adapun untuk analisis data menggunakan teknik analisis deskriptif dan korelasional dengan Structural Equation Model (SEM). Hasil analisis menunjukan, bahwa: 1) tingkat kualitas layanan dalam kategori cukup; 2) kepuasan mahasiswa terhadap layanan dalam kategori cukup; 3) motivasi belajar mahasiswa dalam kategori rendah; 4) tingkat prestasi mahasiswa dalam kategori rendah; 5) ada pengaruh kualitas layanan terhadap kepuasan mahasiswa; 6) ada pengaruh kualitas layanan terhadap motivasi belajar mahasiswa; 7) ada pengaruh tingkat kepuasan terhadap motivasi belajar mahasiswa; 8) motivasi belajar tidak memiliki pengaruh terhadap prestasi mahasiswa; 9) terdapat pengaruh baik langsung maupun tidak langsung antara tingkat kualitas layanan terhadap prestasi melalui motivasi belajar mahasiswa; dan 9) terdapat pengaruh baik secara langsung maupun tidak langsung antara kepuasan terhadap prestasi melalui motivasi belajar mahasiswa.